Cancer Vaccines, Adjuvants, and Delivery Systems - Paston, Samantha J.; Brentville, Victoria A.; Symonds, Peter; Durrant, Lindy G. (Frontiers in Immunology, 2021)
Vaccination was first pioneered in 18th century by Edward Jenner and eventually led to the development of the smallpox vaccine and subsequently the eradication of smallpox. The impact of vaccination to prevent infectious diseases has been outstanding with many infections being prevented and a significant decrease in mortality worldwide. Cancer vaccines aim to clear active disease instead of aiming to prevent disease, the only exception being the recently approved vaccine that prevents cancers caused by the Human Papillomavirus. The development of therapeutic cancer vaccines has been disappointing with many early cancer vaccines that showed promise in preclinical models often failed to translate into efficacy in the clinic. In this review we provide an overview of the current vaccine platforms, adjuvants and delivery systems that are currently being investigated or have been approved. With the advent of immune checkpoint inhibitors we also review the potential of these to be used with cancer vaccines to improve efficacy and help to overcome the immune suppressive tumour microenvironment.